2021
DOI: 10.1051/e3sconf/202131901102
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in uropathogenic enterobacteria

Abstract: Multidrug-resistant Enterobacteriaceae are a major public health threat worldwide. These germs are the most redoubtable because they are producers of beta-lactamases and possess other mechanisms of resistance to many antibiotics. The objective of this work is to identify isolated strains of Enterobacteriaceae and to study their antibiotic resistance profiles, thus contributing to the surveillance of antibioresistance. This is a retrospective study over a period of three years (2018-2020) including urine sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(47 reference statements)
1
2
1
Order By: Relevance
“…20 Penicillin, cephalosporins, trimethoprimsulfamethoxazole, quinolones, carbapenems, aminoglycosides, 2nd, and 3rd generation cephalosporins were the most active compounds against these uropathogens, according to an analysis of non-ESBL generating strains' susceptibility to the antibiotics utilised (E. coli and K.pneumoniae). 21 The finding in our study is similar to the above study. CONCLUSION Alarmingly, 35.9% of inpatients (hospitalized) and 16.9% of outpatients (community) in the current investigation were ESBL-positive, with all extended-spectrum beta-lactamase-producing strains being multi-drug resistant.…”
Section: Results Show That Among 158 Uti Patients: 53supporting
confidence: 92%
“…20 Penicillin, cephalosporins, trimethoprimsulfamethoxazole, quinolones, carbapenems, aminoglycosides, 2nd, and 3rd generation cephalosporins were the most active compounds against these uropathogens, according to an analysis of non-ESBL generating strains' susceptibility to the antibiotics utilised (E. coli and K.pneumoniae). 21 The finding in our study is similar to the above study. CONCLUSION Alarmingly, 35.9% of inpatients (hospitalized) and 16.9% of outpatients (community) in the current investigation were ESBL-positive, with all extended-spectrum beta-lactamase-producing strains being multi-drug resistant.…”
Section: Results Show That Among 158 Uti Patients: 53supporting
confidence: 92%
“…The ticarcillin resistance rate was 95.22%. This is higher than that reported in a study by Jamila et al on antibiotic resistance in uropathogenic enterobacteria [35]. However, the resistance rate to piperacillin + tazobactam was 34.13%.…”
Section: Discussioncontrasting
confidence: 57%
“…Our study found the prevalence of CA-UTIs is 24.27% among symptomatic patients. The observed rate is higher than the levels recorded previously in Italy (20.4%) [17], and in Morocco (17.9%) [18]. UTIs are one of the most common CA-bacterial infectious diseases worldwide, affecting patients of both genders [19].…”
Section: Distribution Of Clinical Isolatesmentioning
confidence: 65%
“…The second most common species were Klebsiella pneumoniae and Proteus mirabilis, each of which was represented by 13 strains (11.20%). Al-Naqshbandi and Chawsheen [23] and Orrett [24] have mentioned similar results for K. pneumoniae and P. mirabilis, respectively [17,18]. Other bacterial species were infrequently isolated, namely Klebsiella oxytoca (n = 3) and Enterobacter cloacae (n = 3) followed by Enterobacter aerogenes (n= 2).…”
Section: Distribution Of Clinical Isolatesmentioning
confidence: 68%